Technical Assistance on Poverty Analysis and Social Statistics : Mission on the Census of Buildings and Dwellings, Voume 4. Questionnaire Design for the Large Sample Household Survey - World Bank (Washington, DC, 2013)
The World Bank is developing a project to develop the capacity of the Central Administration for Statistics (CAS) of Lebanon to produce demographic and social statistics. In the absence of population censuses, the census of buildings and dwelling is one of the few sources of comprehensive data and information at the national level. The census that CAS is planning for 2010-2011 has been identified as an initial candidate for implementation-technical assistance under the current project. The CAS has requested technical support which will run over the life of the Census, from the initiation of the census to the analysis of data, which would extend over the current and the coming fiscal years. In this context, the World Bank organized a one month mission to explore the prospects for this technical assistance. The first two weeks of the mission, Monday 23, March 2009 to Saturday 4, April 2009 focused on assessment. The second two weeks, Monday 6, April 2009 to Saturday 18, April 2009, focused on technical assistance. This note is divided into four volumes. Volume I is an assessment made during the first half of the mission. Volume II addresses the questions related to the Design and Management of the Census of Buildings and Dwellings, drawing from the main conclusions of the assessment phase. Volume III addresses development of the questionnaire for the census of buildings and dwellings. It identifies the recommendations related to the design of the questionnaire(s) that will be used to conduct the next census of buildings and dwellings. Volume IV addresses design of a large-scale household survey (10 percent of households, or 50,000 households) that might be conducted concurrently with the census of buildings and dwellings to generate socio-demographic data of the kind that would be produced by a census of population and housing.